2022
DOI: 10.1007/s44197-021-00023-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ABO Blood Group Phenotype and the Risk of COVID-19 Infection and Severity of Disease in a Saudi Arabian Cohort

Abstract: Background Disease severity among patients infected with SARS-CoV-2 varies remarkably. Preliminary studies reported that the ABO blood group system confers differential viral susceptibility and disease severity caused by SARS-CoV-2. Thus, differences in ABO blood group phenotypes may partly explain the observed heterogeneity in COVID-19 severity patterns, and could help identify individuals at increased risk. Herein, we explored the association between ABO blood group phenotypes and COVID-19 susc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 23 publications
3
19
0
3
Order By: Relevance
“…While several studies failed to reproduce significant associations between ABO blood-type and SARS-CoV-2 infection [ 20 , 60 , [65] , [66] , [67] ], others reached significant associations for blood types other than A and O. Blood type B was related to significantly higher risk of SARS-CoV-2 infection in some studies [ 59 , [68] , [69] , [70] , [71] , [72] , [73] ]; and a meta-analysis indicated that blood type B is associated with higher risk of SARS-CoV-2 infection in Asian, but not in European cohorts [ 74 ]. AB blood type, in turn, has been significantly related to either higher [ 47 , 62 , 68 , [70] , [71] , [72] , [73] , 75 ] or lower [ 59 , 61 ] risk of acquiring COVID-19.…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
See 3 more Smart Citations
“…While several studies failed to reproduce significant associations between ABO blood-type and SARS-CoV-2 infection [ 20 , 60 , [65] , [66] , [67] ], others reached significant associations for blood types other than A and O. Blood type B was related to significantly higher risk of SARS-CoV-2 infection in some studies [ 59 , [68] , [69] , [70] , [71] , [72] , [73] ]; and a meta-analysis indicated that blood type B is associated with higher risk of SARS-CoV-2 infection in Asian, but not in European cohorts [ 74 ]. AB blood type, in turn, has been significantly related to either higher [ 47 , 62 , 68 , [70] , [71] , [72] , [73] , 75 ] or lower [ 59 , 61 ] risk of acquiring COVID-19.…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
“…Blood type B was related to significantly higher risk of SARS-CoV-2 infection in some studies [ 59 , [68] , [69] , [70] , [71] , [72] , [73] ]; and a meta-analysis indicated that blood type B is associated with higher risk of SARS-CoV-2 infection in Asian, but not in European cohorts [ 74 ]. AB blood type, in turn, has been significantly related to either higher [ 47 , 62 , 68 , [70] , [71] , [72] , [73] , 75 ] or lower [ 59 , 61 ] risk of acquiring COVID-19.…”
Section: Associations Between Abo Blood Types and Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…The relationships between ABO blood group antigens and COVID-19 have also been investigated by many researchers. Jawdat et al found that blood group B is a risk factor for COVID-19 and blood group O is protective factor for COVID-19 infection [53]. Zhao et al analyzed the ABO blood group distribution among 2173 COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%